(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article examines the achievements, challenges, and solutions in organizing independent learning in the training of engineering-energy specialists, using the example of the "Fundamentals of Power Supply" course. It highlights advancements in modern technologies, such as virtual laboratories and simulation software, and emphasizes the importance of enhancing students’ independent learning skills. The paper also identifies key challenges, including a lack of technological resources, methodological materials, and assessment systems, while proposing solutions such as integrating modern tools, creating instructional materials, and fostering industry collaboration to improve the educational process.